CTJ In the News (Tufts Archival Research Center, 2007)
Missing Page(s); Collection of Citizens for Tax Justice (CTJ) 1989 articles, studies, and press. Discusses public opinion regarding tax reform. Finds that only 7 large corporations paid no federal taxes in 1988. Adresses 1986 tax reform act. Critixizes current tax proposals for having too many corporate loopholes. Deals with the implications of public opinion on Congress.